Analysis of periarticular bone changes in patients with cutaneous psoriasis without associated psoriatic arthritis. Issue 4 (4th February 2015) - Simon, David; Faustini, Francesca; Kleyer, Arnd; Haschka, Judith; Englbrecht, Matthias; Kraus, Sebastian; Hueber, Axel J; Kocijan, Roland; Sticherling, Michael; Schett, Georg; Rech, Jürgen
Abstract : Objectives: To search for structural bone changes in the joints of psoriasis patients without psoriatic arthritis (PsA). Methods: 55 psoriasis patients without any current or past symptoms of arthritis or enthesitis and 47 healthy controls were examined by high-resolution peripheral quantitative CT scans of the metacarpophalangeal joints. Number, size and exact localisation of erosions and enthesiophytes were recorded by analysing axial scans of the metacarpal heads and phalangeal bases and were confirmed in additional coronal and/or sagittal sections. In addition, we collected demographic and clinical data including subtype, duration and severity of psoriasis. Results: Psoriasis patients showed a larger and significantly increased number of enthesiophytes (total number 306; mean±SD/patient 5.62±3.30) compared with healthy controls (total number 138; mean±SD/patient 3.04±1.81, p<0.001). Enthesiophytes were typically found at the dorsal and palmar sides of the metacarpal heads where functional entheses related to extensor and flexor tendons are localised. Bone erosions were rare and not significantly different between psoriasis patients and healthy controls. If present, erosions were almost exclusively found at the radial side of the second metacarpal head in both psoriasis patients and healthy controls. Conclusions: Psoriasis patients without PsA show substantial signs of enthesiophyte formation compared with healthy controls. These changes represent new bone formation at mechanically exposed sites of the joint and substantiate the concept of the existence of a 'Deep Koebner Phenomenon' at enthesial sites in psoriasis patients.